The Labour Market Situation and Job Quality of Persons With Disabilities Who Participated in Job Activation Programmes in Poland - Smoter, Mateusz; Danilowska, Sylvia (Calitatea Vieții, 2023)
The low level of employment of persons with disabilities is a challenge in all EU countries. Therefore, public policies seek programmes that may help those people find employment. The paper primarily investigates the labour market situation of unemployed people with disabilities who participated in job activation programmes implemented by a country-wide NGO in Poland between 2018−2021. Based on data from a telephone survey conducted six months after the programme, the share of participants who reported good working conditions and satisfaction with their job six months after the programme is presented. The number of programme participants reporting improved self-esteem and social relations is then analysed. Finally, a comparison is made between young and older participants and rural residents and their urban counterparts. The results show that most programme beneficiaries who found a job upon completion of the programme remained in employment six months after the programme, often at the same employer and with a permanent contract. Most participants reported good working conditions and general satisfaction with their job. Less than half reported satisfaction with a salary, which may be due to the low earnings (around the minimum wage level). The results show that young people and urban residents were more often employed in unsheltered workplaces. Also, young people more frequently reported training opportunities at the workplace and less often remained at the same employer. People from rural areas more often reported positive effects of employment on their self-esteem and social relations.